Contract Farming in Tomato Seed Production in Rangpur District of Bangladesh: A Financial Analysis - Sarkar, MAR; Rashid, MHA; Sarker, MR (Progressive Agriculture, 2013)
The present study attempted to determine the contract growers costs and returns of the open pollinated tomato seed production and resource use efficiency under different categories of farmers in some selected areas of greater Rangpur district. In total 60 open pollinated tomato seed contract growers were purposively selected in consultation with BADC personnel at the categories of marginal, small and medium farmers. Total cost, gross margin, gross return, net return and benefit cost ratio (undiscounted) were estimated for financial analysis. The results revealed that per hectare total cost, gross return and net return of open pollinated tomato seed production were estimated at Tk 220313, 384000 and 163687, respectively. Benefit cost ratios came out to be 1.64, 1.74 and 1.83 for marginal, small and medium farmers, respectively which was found a bit higher for the medium open pollinated tomato seed contract growers. The Cobb-Douglas production function model was used to estimate the values of coefficient and related statistics of production function. The coefficient of human labour cost, cost of using seed, organic manure cost, fertilizer cost and irrigation charges were statistically significant. Returns to scale was found to be 1.19 and that of the value of R2 was 0.79. The marginal productivity analysis indicated that the contract growers in the study areas have failed to show their efficiency in using the resources. It was evident that timely and efficient uses of different inputs are most important to increase production and profitability of the open pollinated tomato seed contract growers. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16478 Progress. Agric. 22(1 & 2): 169-179, 2011